Equilibrium ion exchange studies of Zn2+, Cr3+, and Mn2+ on natural bentonite. Issue 57 (7th December 2016) - Stylianou, Marinos A.; Inglezakis, Vassilis J.; Loizidou, Maria D.; Agapiou, Agapios; Itskos, Grigorios
Abstract: Bentonite is a clay mineral often used in ion exchange processes due to its high ion exchange capacity. In the present study, a commercially available in Greece market bentonite was obtained and characterized by XRD, XRF, FTIR, BET, and TG/DTA analysis. Monmorillonite was the main component of bentonite sample (>80%). Ion exchange equilibria of Zn 2+, Cr 3+, and Mn 2+ on bentonite was examined by use of batch equilibrium isotherms, distribution coefficients, and maximum exchange levels (MELs) under the same normality for all metals (0.01 N) at 25 ± 2°C. The equilibrium isotherms for the metals studied exhibit a favorable-type isotherm. Selectivity series deduced from equilibrium isotherms are Cr 3+ > Zn 2+ > Mn 2+, and the same occurs for MELs. The Langmuir and Freundlich models were applied and fitted the equilibrium data for the metal ion uptake. A detailed literature review on heavy metals-bentonite equilibrium is provided.